2014
DOI: 10.4137/cmo.s13410
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Metal Concentration in the Hair of Cancer Patients and Healthy People Living in the Malwa Region of Punjab, India

Abstract: The cancer prevalence in the Malwa region of Punjab (1089/million/year) is much higher than the national average cancer prevalence in India (800/million/year). The participants in the present study were 50 healthy individuals and 49 cancer patients all living in the Malwa region of Punjab, with the healthy people being selected from the same household as the cancer patients. High concentrations of several potentially toxic elements were found in hair samples from people living in Punjab. Compared to standard r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 94 publications
1
27
0
1
Order By: Relevance
“…[8][9][10][11] Eleven casecontrol studies quantified either toenail, hair, blood or urinary arsenic species in breast cancer patients and controls. [12][13][14][15][16][17][18][19][20][21] Generally, the results show a weak or negative correlation with exceptions of reports by Wadhwa et al, and Joo et al, who found arsenic levels to be significantly higher in hair of breast cancer patients as compared to unaffected controls. 21,22 There have been no prospective studies that have examined blood arsenic levels and breast cancer risk.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…[8][9][10][11] Eleven casecontrol studies quantified either toenail, hair, blood or urinary arsenic species in breast cancer patients and controls. [12][13][14][15][16][17][18][19][20][21] Generally, the results show a weak or negative correlation with exceptions of reports by Wadhwa et al, and Joo et al, who found arsenic levels to be significantly higher in hair of breast cancer patients as compared to unaffected controls. 21,22 There have been no prospective studies that have examined blood arsenic levels and breast cancer risk.…”
Section: Introductionmentioning
confidence: 82%
“…Four ecological studies evaluated soil, water or rice contamination with arsenic and local breast cancer rates . Eleven case–control studies quantified either toenail, hair, blood or urinary arsenic species in breast cancer patients and controls . Generally, the results show a weak or negative correlation with exceptions of reports by Wadhwa et al ., and Joo et al ., who found arsenic levels to be significantly higher in hair of breast cancer patients as compared to unaffected controls .…”
Section: Introductionmentioning
confidence: 92%
“…The present study focused on nail metal analysis, a biological material similar to hair. Previously, we had used BJMMR, 5(4): 480-498, 2015; Article no.BJMMR.2015.053 481 ICP-MS spectroscopy to confirm high exposures to aluminium (Al), barium (Ba), manganese (Mn), lead (Pb), uranium (U and other metals in the hair of Punjabi cancer patients and their healthy relatives (Blaurock-Busch et al 2014). In this study, we used nail metal analysis to confirm the results of our previous study.…”
mentioning
confidence: 58%
“…We first tested the nails of the same healthy individuals and cancer patients of Punjab that had previously been selected for our hair study on cancer [33]. Punjabis and 83 healthy Europeans.…”
Section: Participantsmentioning
confidence: 99%
“…Trace mineral patterns in scalp hair samples are providing fruitful data not only as a diagnostic procedure but also in providing answers pertaining to treatment [43]. The mean values with standard deviations of As, Cd, Ni, Se, and Zn in scalp hair of cancerous and referent female subjects are shown in Table 4, which indicates that the levels of toxic elements (As, Cd and Ni) were significantly higher in scalp hair samples of different types of female cancer patients as compared to those results obtained from healthy referent, while reverse pattern was observed in the case of essential trace elements, Se and Zn.…”
Section: Resultsmentioning
confidence: 99%